(untitled) (Annals of Medical Research, 2021)
Aim: Knowledge of blood group distribution and blood serology in a given region is critical for the proper functioning of blood banks and also for delivering the blood products to need owners. We aimed to determine the distribution rates of ABO and Rh blood groups and the incidence of transfusion-transmitted infections in the healthy donors in our region. Materials and Methods: A total of 108,368 healthy individuals were participated in this study. Incidence of HBsAg, anti-HCV, anti-HIV-1/2 and syphilis along with blood group distribution were evaluated retrospectively. Results: Of the blood donors, 98,901(% 91.24) were male and 9,467 (%8.76) were female. Frequency of O, A, B, and AB blood group distribution in the donor population were 31.2%, 44.0%, 16.2%, and 8.6%, respectively. Of the blood donors, 95,039 (87.7%) were Rh positive and 13,229 (12.3%) were Rh negative. A total of 1,685 donors (1.55%) tested positive for HBsAg, 102 (0.09%) for anti-HCV, 23 (0.022%) for anti-HIV-1/2, and 58 (0.05%) tested positive for syphilis.Conclusion: The ABO and Rh blood antigens distribution rates found in our study were similar for male and female and resembled the overall rates for Turkey. When looking at the annual analysis of the donor group, we observed a significant decrease of HbsAg test positivity over a seven-year-period (p values for time periods 2008-2009, 2010-2011, 2012-2013, 2014-2015 were 0.016, 0.02, 0.001, and 0.003 respectively). We believe that our results will be useful for the creation of a database on blood group distribution and the seroprevalence of infectious agents.